The Effect Of The Inquiry Based Learning Model In Improving The Activities Of Grade XI Students In History Learning At SMA Negeri 2 Tenggarong Seberang - Annisa Rahmadhani Khosyi; Norhidayat; Muhammad Sopyan Konsultindo; Sainal A (International Journal of Technology and Education Research, 2026)
This study aims to find out history learning at SMA Negeri 2 Tenggarong Seberang and measure the influence of the application of the Inquiry Based Learning model on the learning activities of grade XI students. The research uses a quantitative approach with a quasi-experimental design in the form of Pretest-Posttest Control Group Design. The research sample was taken by simple random sampling, namely class XI A2 as the experimental class and class XI A1 as the control class (33 students each). Data was collected through observation of student activities, Likert scale questionnaires, and pretest-posttests. The results showed that the activity of students in the experimental class reached 78.75% (Good category), higher than the control class of 66.25% (Adequate category). The validity test of the questionnaire produced 27 valid items with a reliability of Cronbach's Alpha of 0.918. The Independent Sample t-test in the posttest obtained a significance value of 0.027 (< 0.05), so that an alternative hypothesis was accepted. Based on these results, it can be concluded that the Inquiry Based Learning learning model has a significant effect on improving the learning activities of grade XI students in History learning at SMA Negeri 2 Tenggarong Seberang. This model is able to create more active, interactive, and compliant learning with the Independent Curriculum.